La calidad educativa: una mirada desde los testimonios de Santa Rosa de Lima y de Víctor Andrés Belaúnde - Elgegren Reátegui, Fernando (2010)
The educational quality offered by the UNIFÉ, in the area of education, is view under the light of an analogy between the life of Santa Rosa de Lima, Patron-Saint of UNIFE's educationschool, and sorne ideas on what higher education should be about as proposed by Víctor Andres Belaunde Diez Canseco - doctor of History, Philosophy and Arts by San Marcos University - in his book Meditaciones Peruanas (Peruvian Meditations) (MP, 1963) and, specifically, in his essay about university problem that is part of Realidad Nacional (National Reality), a book whose third edition dates back from 1963, a year before the creation of UNIFE.